2018
DOI: 10.3390/ijfs6020040
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Revenue Diversification on Bank Profitability and Stability: Empirical Evidence from South Asian Countries

Abstract: This paper is a contribution to the ongoing debate on the benefits and drawbacks of bank revenue diversification. Revenue diversification may benefit banks if diversified activities are inherently less risky and possess high returns, while it may hurt banks if diversified activities are more risky and have low returns. Analyzing a panel dataset of 200 commercial banks from all South Asian countries, we found that overall revenue diversification into non-interest income has a positive impact on the profitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
8
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 49 publications
8
57
8
5
Order By: Relevance
“…Arising from the empirical result, we therefore accept the null hypothesis (H02) that foreign exchange income has no significant positive effect on liquidity of Nigerian deposit money banks. This finding is in contrast with that of Nisar et al(2018) which found that other noninterest income exerts positive influence on performance of Asian Banks.…”
Section: Journal Of Accounting Finance and Auditing Studies 5/2 (201contrasting
confidence: 99%
See 1 more Smart Citation
“…Arising from the empirical result, we therefore accept the null hypothesis (H02) that foreign exchange income has no significant positive effect on liquidity of Nigerian deposit money banks. This finding is in contrast with that of Nisar et al(2018) which found that other noninterest income exerts positive influence on performance of Asian Banks.…”
Section: Journal Of Accounting Finance and Auditing Studies 5/2 (201contrasting
confidence: 99%
“…The implication of the findings is that banks in Nigeria do not derive sufficient income from commission and any attempt by them to increase the revenue from this source may shift banks attention away from other veritable sources of income generation which will reduce the overall income of the bank and thus reduce the liquidity. This finding is in line with that of Nisar et al (2018)which found…”
Section: Journal Of Accounting Finance and Auditing Studies 5/2 (201supporting
confidence: 93%
“…Trading income (TRAD) has shown a negative relationship with risk, which is not consistent with [4,9,14]. Other non-interest income shows a positive relationship with risk, which is not consistent with [4,14,19].…”
Section: Resultsmentioning
confidence: 87%
“…The most recent research is conducted by Moudud-Ul-Huq, et al [16] support that the diversification of income benefits the bank by improving performance and reducing risks. The study [19] shows that non-interest income as a whole is reducing bank risk in South Asia. Diversification is important because it increases bank income and also decreases the possibility of such pressure as the bank crisis [7].…”
Section: Literature Reviewmentioning
confidence: 92%
“…Haidary and Abbey (2018) found that there was no influence between liquidity and ROA which indicated the number of bad loans illustrating that loans provided had less impact on bank income. Different results found by Nisar, Peng, Wang, and Ashraf (2018) and Al-Tamimi (2010), states that there is a positive and significant effect between liquidity and ROA which indicates the higher the amount of the loan, the higher the bank gets a profit in the form of credit interest. When banks have a lot of capital customers, they tend to make loans, thereby increasing bank profits.…”
Section: Liquiditymentioning
confidence: 79%